Retinal atrophy, inflammation, phagocytic and metabolic disruptions develop in the MerTK-cleavage-resistant mouse model - Enderlin, Julie; Rieu, Quentin; Réty, Salomé; Vanoni, Elora M.; Roux, Solène; Dégardin, Julie; César, Quénol; Augustin, Sébastien; Nous, Caroline; Cai, Bishuang; Fontaine, Valérie; Sennlaub, Florian; et al. (Frontiers in Neuroscience, 2024)
In the eye, cells from the retinal pigment epithelium (RPE) facing the neurosensory retina exert several functions all crucial for long-term photoreceptors (PRs) survival and vision. Among those, RPE cells phagocytose under a circadian rhythm photoreceptor outer segment (POS) tips that are constantly subjected to light rays and oxidative attacks. The MerTK tyrosine kinase receptor is a key element of this phagocytic machinery required for POS internalization. Recently, we showed that MerTK is subjected to the cleavage of its extracellular domain as a way of finely controlling its function. As well, monocytes in retinal blood vessels can migrate inside the inner retina and differentiate into macrophages expressing MerTK, but their role in this context has not been studied yet. We thus investigated the ocular phenotype of MerTK cleavage-resistant (MerTKCR) mice in order to understand the relevance of this characteristic on retinal homeostasis both at the RPE and macrophage levels. MerTKCR retinae appear develop and function normally as observed on retinal sections, by electroretinogram recordings and optokinetic behavioral tests. Monitoring of MerTKCR and control mice between the ages of 3 and 18 months showed the development of large degenerative areas in the central retina as early as 4 months when followed monthly by optical coherence tomography (OCT) plus fundus photography (FP)/autofluorescence (AF) detection but not by OCT alone. The degenerative areas were associated with AF that seem to be due to infiltrated macrophages as observed by OCT and histology. MerTKCR RPE primary cultures phagocytosed less POS in vitro while in vivo the circadian rhythm of POS phagocytosis was deregulated. Mitochondrial function and energy production were reduced in freshly dissected RPE/choroid tissues at all ages, thus showing a metabolic impairment that was not present in macrophages. RPE anomalies were detected by electron microscopy including phagosomes retained in the apical area and vacuoles. All together, this new mouse model displays a novel phenotype that could prove useful to understand the interplay between RPE and PRs in inflammatory retinal degenerations and highlights new roles for MerTK in the regulation of the energetic metabolism and the maintenance of the immune privilege in the retina.